WATER QUALITY INVESTIGATION OF BUTUANON RIVER: AN ASSESSMENT OF ITS FECAL INDICATOR BACTERIA (Fecal Coliforms and Total Coliforms) AND PHYSICOCHEMICAL PROPERTIES IN CEBU CITY LOCATIONS ONLY - Macawile, Sheila Marie; Sumalpong, Sharika June; Reyes, Debbie; Siojo, Chloe Naty Marie Eugenie; Bustamante, Jeson (Asian Journal Of Medical Technology, 2025)
Cebu’s Butuanon River is under investigation as potential water source, but declining water quality poses risks to human and animal health. This study investigates its fecal indicator bacteria (FIB), specifically fecal and total coliforms, and physicochemical properties within Cebu City’s borders. Utilizing analytical cross-sectional design and purposive sampling, researchers collected samples from upstream (Pulang-Bato), midstream (Bacayan Bridge-Biofence), and downstream (Talamban Bridge-Sitio Tintay) for laboratory testing. FIB levels were determined using the Multiple Tube Fermentation Technique (MPN/100 mL), while Biochemical Oxygen Demand [BOD] was determined using the 5-day BOD test, Dissolved Oxygen [DO] using Azide Modification, and Total Suspended Solids [TSS] with Gravimetric Analysis. Data were treated using mean, standard deviation, SPSS version 29 for statistical analysis. Findings revealed lower fecal coliform levels in the upstream, with increasing levels in the midstream and downstream, whereas, total coliforms are constant among the three sampling sites. Physicochemical properties failed to meet the Class C water quality criteria set by the DAO 2016-08, indicating significant microbial pollution. No significant differences were found in mean FIB, BOD, DO, and TSS levels among sites, but a significant relationship existed between water quality and FIB levels, indicating the need for interventions to improve the river’s water quality.